Approximation to the Consumption of Healthcare Resources and the Economic Cost of SARS-CoV-2 Patient Management: A Retrospective Study - Calderón-Moreno, Jesús; Juárez-Vela, Raúl; Delgado-Rodríguez, María Jesús; Quintana-Díaz, Manuel; Magallón-Botaya, Rosa; Olivan-Blázquez, Bárbara; Cobos-Rincón, Ana; Santolalla-Arnedo, Iván; Ramírez-Torres, Carmen Amaia; Gea-Caballero, Vicente; Andrés-Esteban, Eva María (Frontiers in Public Health, 2022)
Spain has become one of the countries most affected by the disease, one of the countries with the highest COVID-19 testing rates, and one of the worst-performing countries in the fight against the sars-CoV-2 pandemic. There are no studies related to the consumption of health resources and the economic cost of the SARS-CoV-2 virus. We presented a retrospective analysis of 9811 (Primary Care and Hospital) patients which aimed to estimate approximate public health expenditure and the consumption of health resources by COVID-19. Attending to the results, the gender distribution of patients has a similar rate in both groups, with slightly higher rates in women. Similarly, age is the same in both groups, with a median of 62 years in the case of hospitalizations and 61 years in the case of primary care; using a weighted average of these rates and costs, we can estimate that the average cost of care per patient infected with the SARS-CoV-2 virus, regardless of their course, was 2373.24€ per person. We conclude that a patient with COVID-19 without hospitalization is € 729.79, the costs of a hospitalized patient are € 4,294.36, and € 14,440.68 if there is ICU admission